(untitled) (Journal of Hama University, 2026)
Psychological violence against children is one of the oldest social phenomena that has accompanied human history, and it continues in various forms and patterns to this day. This persistence has prompted many researchers to investigate and study violent behavior of all kinds, with the goal of identifying its most prominent causes and the factors that lead to it. As a result, several interpretations of psychological violence have emerged, varying according to the various theoretical approaches that have studied and analyzed it. By reviewing the theoretical legacy related to psychological violence, it becomes clear that the psychological approach is one of the most prominent research aspects that has attempted to analyze and understand this phenomenon and identify the reasons for its spread at various levels of society, whether in institutions, in public places, or at the individual level, in addition to addressing ways to confront it. Accordingly, this study will address the concept of psychological violence against children in its various forms, highlighting a set of related concepts. It will also review various theories within the framework of the psychological approach to violence, which seek to explain this phenomenon and understand its dynamics and development.